Use of excel worksheets with user-friendly interface to minimize the makespan in a permutation flow shop production system - Rocha, Rony Peterson da; Ravagnani, Mauro Antônio Silva Sá; Andrade, Cid Marcos Gonçalves; Paraíso, Paulo Roberto (Acta Scientiarum. Technology, 2014)
Current research addresses the Permutation Flow Shop scheduling problem, characterized as Production Scheduling in Batch Process (PSBP) to minimize total time to complete the schedule (Makespan). A method to approach the problem of production scheduling is to turn it into Mixed Integer Linear Programming (MILP) and to solve it by using commercial mathematical programming packages. An electronic spreadsheet with user-friendly interface (ESUFI) was developed in Microsoft Excel. Results showed that it is possible to use ESUFI to solve small problems. Â 